Sliding instability characteristics and re-stabilization mechanism of key stratum in thin-topsoil SCS mining: a computer-aided case study from the Niushan Coal Mine, China - Gong, Peilin; Zhao, Tong; Yetilmezsoy, Kaan; Yi, Kang (SPRINGER, 2020)
Roof step subsidence and support crushing accidents caused by the sliding instability of fractured single key stratum often occur in shallow coal seam (SCS). For this reason, the exploration of fracture displacement laws and control mechanism of key stratum in thin-topsoil SCS is of great significance for both roof control and safety production. From this perspective, in this study, numerical simulation and theoretical analysis were conducted to establish a mechanical model of the key stratum structure after sliding instability in thin-topsoil SCS. Moreover, its instability characteristics and re-stabilization control mechanism were analyzed. The results revealed that the fractured key stratum block could reach re-stabilization without any support crushing after sliding instability in thin-topsoil SCS depending on the significant unloading effect of the topsoil. The mechanical model of the key stratum structure after sliding instability was also analyzed to obtain the criterion for the restabilization of the sliding instable rock block. The computational analysis corroborated that increasing the support intensity could promote the re-stabilization of fractured key stratum block after sliding instability, and the required support working resistance could be obtained for preventing support crushing incidents.
Keywords: Thin-topsoil SCS; Sliding instability characteristics; Re-stabilization mechanism; Support intensity; Mechanical model; SHALLOW; SEAM; Environmental Sciences & Ecology; Geology; Water Resources